2010
DOI: 10.1111/j.1468-3083.2010.03834.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reflectance confocal microscopy: automated diagnostic image analysis of melanocytic skin tumours

Abstract: The automated RCM image analysis procedure holds promise for further investigations. However, to date our system cannot be applied to routine skin tumour screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…To address the need for training, machine learning-based image analysis is being investigated to provide quantitative and objective approaches for reading images. (Gareau et al, 2010; Koller et al, 2011; Kurugol et al, 2011; Wiltgen et al, 2008) One of the first studies reported a method based on texture analysis for automated identification of diagnostically significant regions in RCM images of melanocytic lesions(Koller et al, 2011; Wiltgen et al, 2008). Another group of researchers developed a method to automatically quantify the spread of pagetoid melanocytes in epidermis and disarray at the DEJ level in order to detect superficial spreading melanomas (Gareau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To address the need for training, machine learning-based image analysis is being investigated to provide quantitative and objective approaches for reading images. (Gareau et al, 2010; Koller et al, 2011; Kurugol et al, 2011; Wiltgen et al, 2008) One of the first studies reported a method based on texture analysis for automated identification of diagnostically significant regions in RCM images of melanocytic lesions(Koller et al, 2011; Wiltgen et al, 2008). Another group of researchers developed a method to automatically quantify the spread of pagetoid melanocytes in epidermis and disarray at the DEJ level in order to detect superficial spreading melanomas (Gareau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These assessment approaches have focused on one of three main categories: 1) Quantifying and detecting specific features such as counting keratinocytes [5], detecting pagetoid cells [6] and evaluating photoageing [7], 2) Computer aided diagnosis of malignant melanocytic lesions [8] and 3) Identifying the anatomical structures of human skin [9,10]. Although both Somoza et al and Kurugol et al considered the problem of understanding human skin their work is limited: Kurugol et al consider only the location of the dermal-epidermal junction and showed good performance only in darker skin types: 89% of the epidermis and 87% of the dermis were correctly classified in dark skin, whereas in light skin only 64% and 75% of the epidermis and dermis were correctly classified.…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison of dermoscopy to RCM found no significant difference between the sensitivity and specificity for melanoma between these two methods [56]. Attempts have also been made to integrate automated computer analysis with RCM images and have resulted in 93.6% sensitivity and 90.4% specificity for melanoma detection in learning sets [66]. An additional strength of RCM is the ability to identify amelanotic lesions [67] and early melanoma in situ with a sensitivity of 85% and specificity of 76% for these tumors [68,69].…”
Section: Reflectance Confocal Microscopy and The Vivascopementioning
confidence: 99%